Introduction to Logic
Given ∀x.∀y.∀z.(p(x,y) ∧ p(y,z) ⇒ p(x,z)), ∀x.p(x,a), and ∀y.p(a,y), use Relational Resolution to prove ∀x.∀y.p(x,y).
Show Instructions
To apply a rule of inference, check the lines you wish to use as premises and click the button for the rule of inference. Reiteration allows you to repeat an earlier item. To delete one or more lines from a proof, check the desired lines and click Delete. Note that factoring and resolution are implemented here as separate rules of inference.
Whenever entering expressions, use Ascii characters only. Use ~ for ¬; use { and } for sets. For variables use strings of alphanumeric characters that begin with a capital letter. For example, to enter the sentence {¬p(x), q(y)}, write {~p(X), q(Y)}.
1
{~p(X,Y),~p(Y,Z),p(X,Z)}
Premise
2
{p(X,a)}
Premise
3
{p(a,Y)}
Premise
4
{~p(b,c)}
Negated Goal
5
{~p(b,V35),~p(V35,c)}
Resolution
1
4
6
{~p(a,c)}
Resolution
2
5
7
{}
Resolution
3
6
